Africa and the Common Market - Okigbo, P. N. C. (Evanston : Northwestern University Press, 1967)
With the conclusion of the Nigerian negotiations and the wide interest they evoked, especially abroad, the author came to realize that the discussion of the problem posed for Africa by the establishment of the European Economic Community would be of interest to students of international economics and economic relations
Includes index
osc 31/10/2018
Loans
Keywords: Africa